Efektivitas Penggunaan Media Sosial Tiktok terhadap Hasil Belajar Siswa di SDN 36 Lubuk Pasing Pesisir Selatan - Kurniawan, Aldi; Alfurqan, Alfurqan (FONDATIA, 2023)
This study aims to see whether the use of social media TikTok is effective in increasing the learning outcomes of class VI students in subject matter of Islamic Religious Education at the Public Elementary School of 36 Lubuk Pasing, Bayang, Pesisir Selatan. Quantitative research and experimental methods are used in this study. Pre-test and post-test, as well as observation with a sample of 18 students, were used as data collection methods. After that, students were divided into two groups, with half of each group representing the experimental group and the other half representing the control group. Analytic prerequisite tests, such as normality tests and homogeneity tests, are used in data analysis techniques. The T-test or paired sample T-test is then used to test the hypothesis. The results of the research in the experimental group and the control group for the 2022/2023 academic year show that the experimental group obtained the highest score from the research analysis. This is evidenced in the 85–90 range, where there were 4 students, or 44.4%, with an average post-test of 80.56, while the control group got an average of 48.89. The consequences of the examination in the trial group after being given the treatment and the post-test were carried out to get a typical value of 80.56, which is classified as very high. A Sig (2-tailed) value of 0.05 was obtained after calculating the hypothesis test with the help of SPSS version 22 and paired sample t-tests. Therefore, it can be concluded that student learning outcomes increase and are different when using TikTok compared to students who don't. Therefore, the more various media used for learning Islamic religious education, the more likely it is to improve student learning outcomes, and students are increasingly motivated to study in order to achieve high learning outcomes.